THE PARADOX OF EDUCATION REFORMS – THE EXAMPLE OF SERBIA - Pljakić, Goran D (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
The author addresses the issue of paradoxicality of educational reforms implemented in Serbia since the year two thousand. The strategic goal of the reforms is democratization of the educational system which is meant to provide fundamental support for the development of a democratic society. However, the question arises of how to develop such a system in light of the fact that a democratic society is a precondition for the development of a democratic educational system. In this case the paradox lies in the fact that expected outcomes of educational reforms are also preconditions for their implementation. The paper also deals with actual outcomes of completed reforms of educational systems in our country. The author points out that apparent problems in strategic planning of educational reforms, among other, stem from obvious oversights concerning anticipation of economic, cultural and social development, as well as overall social and civilisational developments expected in the period ahead.
Keywords: educational reform; paradox; strategic planning; democratic society